Human sexuality education and the family. - NICHOLSON, George D. (1994)
Reports a prevalence of parental ignorance and ambivalence with their own sexuality and embarrassment at providing more than partial explanations, if any at all, for their children. Concludes that it is unrealistic to depend on the family for human sexuality education, and that what is required is the concerted effort of home and school, parent and teacher, to sexually empower young people to make choices for adulthood.